E-031 Radial access for cerebrovascular intervention using penumbra benchmark 071 guiding catheter. (22nd July 2018) - Satti, S; Rastogi, S; Eden, T; Vance, A
Abstract : Introduction: Radial access is increasingly being considered as first line access for neurovascular interventions. Currently, there are no dedicated guiding catheters designed for neurovascular procedures via radial approach. We sought to evaluate technical success, complications, and efficiency when using the Penumbra Benchmark 071 inch guiding catheter in conjunction with Penumbra Select diagnostic catheters for neuro interventional procedures. Methods: A single-center retrospective review over 2 year period (1/2016 to 3/2018) of consecutive radial access procedures (using a 6F sheath) was performed via electronic query in patients undergoing neurovascular intervention when a Benchmark guiding catheter was used. Patient demographics, equipment, time from radial access to target vessel catheterization, procedure times, and complications were identified. Results 28 patients undergoing cerebrovascular intervention met criteria for inclusion. There was 100% technical success in accessing the target vessel using radial access as the first line approach. Average age: 63 Gender: 75% Female Target vessel: Right internal carotid artery −32%, left internal carotid artery – 36%, vertebral artery −25% Time from radial access to target vessel access: 14 min (including 2 patients with 37 and 33 min access required for LICA). Procedures: Aneurysm treatment 10/28 (36%) primary coiling 2/28 (7%) Balloon assisted coiling (*1 patient was BAC with PED) 8/28 (29%) Stent-assisted coiling 4/28 (14%) Pipeline embolization] 2/28 (7%) Intracranial stenting Wingspan 1/28 (4%) AVM or dural AV fistula embolization 1/28 (l4%) Left Subclavian Stent Complications: With the exception of mild non-flow limiting spasm, no major catheter-related complications (iatrogenic dissection) or radial access site complications were encountered. No patients required conversion from radial to femoral access. One patient had in-stent thrombosis which was successfully treated with IA infusion of IIBIIA; no associated permanent neurologic deficits. Discussion: Although not specifically designed for radial access, the Penumbra Benchmark 071 inch guiding catheter, we were able to use it to perform 32 consecutive neurovascular procedures without major access site or catheter related complication. When the catheter is placed in a high proximal intracranial position, there is sufficient internal diameter and a stable proximal construct can be established to perform a wide range of complex neurovascular interventions including pipeline embolization, balloon assisted coiling, and arteriovenous malformation embolization. Conclusion: The Penumbra Benchmark 071 guiding catheter can be used to perform neurovascular interventions via a radial access and was found to be atraumatic, easily trackable, flexible and stable, with a large enough ID to perform most cerebrovascular procedures. Disclosures: S. Satti: 2; C; Stryker Neurovascular, Penumbra Neurovascular. S. Rastogi: None. T. Eden: None. A. Vance: None.